Pseudepigraphic Paulines in the New Testament - Verhoef, Eduard (HTS teologiese studies, 2003)
In order to verify the presence of pseudepigraphic epistles in the New Testament, scholars have often argued that followers of a famous philosopher, such as Pythagoras or Plato, wrote pseudepigraphic do-cuments. This argument presumes that pseudepigraphy was an accepted phenomenon in antiquity and that the writing of epistles under someone else's name was socially not offensive. In this article, this presumption is questioned. The article shows that writers could be banished or put to death if it was the intention of their writings to deceive their audience as far as the identity of the author thereof. As epistles are distinguished from short stories or poems, writings which were written with the intention of deceiving their readers should be set apart from those without such an intention. In view of this distinction the article establishes categories of “Pauline” epistles in the New Testament. The aim is to argue that there are indeed epistles which intended to deceive their readers with regard to “Pauline” authorship. The legitimacy of these epistles would have been rejected on account of their pseudepigraphic nature.